Primordial black holes from effective field theory of stochastic single field inflation at NNNLO - Sayantan Choudhury; Ahaskar Karde; Pankaj Padiyar; M. Sami (European Physical Journal C: Particles and Fields)
Abstract We present a study of the Effective Field Theory (EFT) generalization of stochastic inflation in a model-independent single-field framework and its impact on primordial black hole (PBH) formation. We show how the Langevin equations for the “soft” modes in quasi de Sitter background is described by the Infra-Red (IR) contributions of scalar perturbations, and the subsequent Fokker–Planck equation driving the probability distribution for the stochastic duration $$\mathcal {N}$$ N , significantly modify in the present EFT picture. An explicit perturbative analysis of the distribution function by implementing the stochastic- $$δ N$$ δ N formalism is performed up to the next-to-next-to-next-to-leading order (NNNLO) for both the classical-drift and quantum-diffusion dominated regimes. In the drift-dominated limit, we perturbatively analyse the local non-Gaussianity parameters $$(f_NL, g_NL, τ _NL)$$ ( f NL , g NL , τ NL ) with the EFT-induced modifications. In the diffusion-dominated limit, we numerically compute the probability distribution featuring exponential tails at each order of perturbative treatment.